2012
DOI: 10.1134/s1070428012010101
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-substituted 2-azaspiro[4.5]deca-6,9-dien-8-ones and 2-azaspiro[4.5]deca-1,6,9-trien-8-ones by condensation of 2,6-dimethylphenol with isobutyraldehyde and nitriles

Abstract: 1-Substituted 3, 3,7,9-tetramethyl-2-azaspiro[4.5]deca-6,9-dien-8-ones and 3,3,7,9-tetramethyl-2-azaspiro[4.5]deca-1,6,9-trien-8-ones were synthesized by three-component condensation of 2,6-dimethylphenol with isobutyraldehyde and nitriles in concentrated sulfuric acid.Compounds having a 2-azaspiro[4.5]decane skeleton rarely occur in nature. Examples of such structures are annosqualine isolated from the Stems of Annona squamosa [1], spirostaphylotrichins produced by Staphylotrichum coccosporum [2][3][4], triti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Radical cyclization is an important aspect of radical reactions . Recognition of the importance of radical cyclization in organic synthesis has increased with the development of radical chemistry. Presently, such a technique often enables access to very complex carbocyclic and heterocyclic compounds. In various radical cyclizations, investigators have found that some given axially chiral radicals can cyclize to give ring-closure products with not only high regioselectivity but also high stereoselectivity, , that is, the axially chiral element disappears in the reaction processes, accompanied by the formation of a certain stereocenter in the resulting product structure, often termed a “transfer of chirality”. Chirality transfer is a type of “memory of chirality”, in which the stereochemical elements in the products and reactants are different.…”
Section: Introductionmentioning
confidence: 99%
“…Radical cyclization is an important aspect of radical reactions . Recognition of the importance of radical cyclization in organic synthesis has increased with the development of radical chemistry. Presently, such a technique often enables access to very complex carbocyclic and heterocyclic compounds. In various radical cyclizations, investigators have found that some given axially chiral radicals can cyclize to give ring-closure products with not only high regioselectivity but also high stereoselectivity, , that is, the axially chiral element disappears in the reaction processes, accompanied by the formation of a certain stereocenter in the resulting product structure, often termed a “transfer of chirality”. Chirality transfer is a type of “memory of chirality”, in which the stereochemical elements in the products and reactants are different.…”
Section: Introductionmentioning
confidence: 99%
“…We began by examining the feasibility of applying the G-2 -mediated ATRC to anisole derivatives bearing a trichloroacetamide handle (i.e., 1 ) to achieve 1-azaspiro[4.5]decane compounds. , On the basis of our previous results in dearomatizing radical spirocyclization upon inactivated benzene promoted by Cu(I), we used the tert -butyl derivative 1a as the substrate. The required trichloroacetamide 1a was prepared through imine formation from 4-methoxybenzaldehyde and tert -butylamine, followed by reduction and trichloroacetylation.…”
mentioning
confidence: 99%
“…In continuation of our studies on the reactions of 5-arylfuran-2,3-diones with spirans of the 2-azaspiro- [4.5]deca-1,6,9-trien-8-one series in the present work we examined how additional substituents in positions 3 and 6 of the latter affect the direction of their reaction with the former. 5-Arylfuran-2,3-diones Ia and Ib reacted with 2-azaspiro [4.5]deca-1,6,9-trien-8-ones IIa-IId [8][9][10] at a molar ratio of 1 : 1 on heating in boiling benzene (3-6 h, TLC monitoring) to afford (2Z,5Z)-1-aryl-3hydroxy-5-(5′,5′-dimethyl-4-oxo-2′H,4H-spiro[naphthalene-1,3′-pyrrolidin]-2′-ylidene)pent-2-ene-1,4-diones IIIa and IIIb and substituted (2Z,5Z)-3-hydroxy-5-(3,3-dimethyl-8-oxo-2-azaspiro [4.5]deca-6,9-dien-1ylidene)-1-phenylpent-2-ene-1,4-diones IIIc-IIIe (Scheme 1). The structure of compound IIIe was confirmed by X-ray analysis.…”
mentioning
confidence: 99%